Enhancing Music Notation Literac The Impact of Keyboard Media on Students’ Ability to Read and Apply Music Notation - prasetyo, shaffatasya; Sadhana, Senyum (Solah, 2025)
The teaching of staff notation in music is often perceived as abstract and confusing by students, especially when delivered solely through theoretical methods without sufficient practical support. This study aims to describe the process and outcomes of learning to read staff notation using the keyboard as a practical medium among 12th-grade students (Class XII-1.2) at SMA Negeri 11 Surabaya. This research employs a descriptive qualitative method, with data collected through observation, documentation, and individual performance assessments. The study involved 30 students as research subjects. The findings indicate that the use of the keyboard as a music learning tool significantly enhances students’ understanding of staff notation. Students were better able to associate musical symbols with concrete pitches through direct practice. Furthermore, the learning process became more engaging and active, contributing to increased learning motivation (affective domain), improved accuracy in reading and playing notation (cognitive and psychomotor domains), and greater confidence in musical performance. The keyboard also facilitated individual participation, both in independent practice and performance assessments. In conclusion, media-based learning strategies such as the keyboard effectively bridge the gap between theory alternative in arts and culture education.